2021
DOI: 10.3390/plants10071348
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Promises of Medicinal Plants in Bangladesh and Their Bioactive Compounds against Ulcers and Inflammatory Diseases

Abstract: When functioning properly, the stomach is the center of both physical and mental satisfaction. Gastrointestinal disorders, or malfunctioning of the stomach, due to infections caused by various biological entities and physiochemical abnormalities, are now widespread, with most of the diseases being inflammatory, which, depending on the position and degree of inflammation, have different names such as peptic or gastric ulcers, irritable bowel diseases, ulcerative colitis, and so on. While many synthetic drugs, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 198 publications
(204 reference statements)
0
19
0
Order By: Relevance
“…To overcome the resistance problem, new drugs for H. pylori infection are urgently required. Medicinal plant and herb extracts, including extracts from Artemisia annua and Artemisia douglasiana, possess activity against H. pylori infection [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ], and their effect could be considered an important alternative or adjuvant therapeutic approach. Previous studies [ 49 ] demonstrated that artemisinin and a series of semisynthetic analogues were effective against drug sensitive and resistant H. pylori strains.…”
Section: Discussionmentioning
confidence: 99%
“…To overcome the resistance problem, new drugs for H. pylori infection are urgently required. Medicinal plant and herb extracts, including extracts from Artemisia annua and Artemisia douglasiana, possess activity against H. pylori infection [ 42 , 43 , 44 , 45 , 46 , 47 , 48 ], and their effect could be considered an important alternative or adjuvant therapeutic approach. Previous studies [ 49 ] demonstrated that artemisinin and a series of semisynthetic analogues were effective against drug sensitive and resistant H. pylori strains.…”
Section: Discussionmentioning
confidence: 99%
“…from different altitudes of Kashmir Himalaya and studied by using different morphometric parameters (using standard techniques). Rheum emodi is a perennial plant that grows from thick and erected rhizomes and as well as from long roots [5,7,17]. R. spiciforme is also a stout herb.…”
Section: Discussionmentioning
confidence: 99%
“…This increase in the number of platelets shortens blood clotting time and helps treat jaundice. It, therefore, has a truly cleansing action upon the gut, removing debris and then astringing with antiseptic properties [16,17].…”
Section: Medicinal Properties Of Rheummentioning
confidence: 99%
“…Its leaf, bark, and seed are used for therapeutic purposes. Numerous biological and pharmacological activities of neem leaf has been reported including antibacterial ( 13 ), antifungal ( 14 ), and anti-inflammatory activities ( 15 ). Neem leaf extract potently inhibits many bacteria such as S. mutans , Enterococcus faecalis , and Candida albicans in biofilm ( 16 ), Lactobacillus spp .…”
Section: Introductionmentioning
confidence: 99%